Earning differentials between German and French speakers in Switzerland - Alejandra Cattaneo; Rainer Winkelmann (University of Zurich, Socioeconomic Institute, 2003)
The paper analyzes the effect of mother tongue on labor market outcomes of Swiss residents. This type of analysis can shed light on an important policy question. Is the Swiss labor market well integrated, or can one find instead segmentation along language borders? Improving on previous research in this area, we use a nationally representative household survey, the Swiss Household Panel 1999 and 2000, and we explicitly account for self-selection of workers into language areas. Overall, we find no evidence to suggest that the Swiss labor market is not perfectly integrated or that internal migrants are positively selected.
Keywords: J1; J31; J4; J7; 330; language; labor market segmentation; Swiss household panel; Sprache; Arbeitsmarktsegmentierung; Einkommensverteilung; Schätzung; Schweiz